Does central bank transparency and communication affect financial and macroeconomic forecasts? - Thomas Lustenberger; Enzo Rossi (University of Basel, Center of Business and Economics (WWZ), 2018)
In a large sample of countries across different geographic regions and over a long period of time, we find limited country- and variable-specific effects of central bank transparency on forecast accuracy and their dispersion among a large set of professional forecasts of financial and macroeconomic variables. More communication even increases forecast errors and dispersion.
Keywords: C23; C53; E37; E58; D8; 330; central bank transparency; central bank communication; central bank independence; inflation targeting; forward guidance; macroeconomic forecasts; financial forecasts; panel data models with truncated data